Pengaruh Pemberian Kuis di Awal Pertemuan dalam Model Pembelajaran Inkuiri Terbimbing terhadap Hasil Belajar Peserta Didik Kelas XI MIA SMAN 10 Gowa (Studi pada Materi Pokok Asam Basa) - Aldiansah, Andi Faldi; Anwar, Muhammad; Side, Sumiati (Jurusan Kimia FMIPA UNM, 2021)
This study is a quasi-experimental study that aims to determine the effect of giving quiz at the beginning of a meeting in a guided inquiry learning model towards the students outcomes of Class XI MIA SMA Negeri 10 Gowa. The population of this study was students of class XI MIA SMA Negeri 10 Gowa consisting of 4 XI MIA classes totaling 128 people. The sampling technique used a random sampling technique. The data obtained from the research results provided by the test of learning outcomes which were obtained on average in the experimental class were 81.10 and the control class was 70.63. The results of inferential statistical analysis obtained tcount (4.03)> t table (3.10) at α ═ 0.05. Quiz at the beginning of the meeting in the guided inquiry learning model affect the student outcomes of Class XI MIA SMA Negeri 10 Gowa study of basic acid base material.